The emerging role of glutamine as an indicator of exercise stress and overtraining - Rowbottom, D. G.; Keast, D.; Morton, A. R. (Sports Medicine, 1996)
Glutamine is an amino acid essential for many important homeostatic functions and for the optimal functioning of a number of tissues in the body, particularly the immune system and the gut. However, during various catabolic states, such as infection, surgery, trauma and acidosis, glutamine homeostasis is placed under stress, and glutamine reserves, particularly in the skeletal muscle, are depleted. With regard to glutamine metabolism, exercise stress may be viewed in a similar light to other catabolic stresses. Plasma glutamine responses to both prolonged and high intensity exercise are characterised by increased levels during exercise followed by significant decreases during the post-exercise recovery period, with several hours of recovery required for restoration of pre-exercise levels, depending on the intensity and duration of exercise. If recovery between exercise bouts is inadequate, the acute effects of exercise on plasma glutamine level may be cumulative, since overload training has been shown to result in low plasma glutamine levels requiring prolonged recovery. Athletes suffering from the overtraining syndrome (OTS) appear to maintain low plasma glutamine levels for months or years. All these observations have important implications for organ functions in these athletes, particularly with regard to the gut and the cells of the immune system, which may be adversely affected. In conclusion, if methodological issues are carefully considered, plasma glutamine level may be useful as an indicator of an overtrained state.